The third option - Flynn, Vince (New York : Pocket Star Books, 2001)
CIA counterterrorism expert Mitch Rapp is sent on a mission to stop a German industrialist selling sensitive materials to a terrorist sponsor, unaware that he is being set up by forces in Washington who will do anything to see him fail.
NCBA
Keywords: Conspiracies -- Fiction; Political fiction